Hubungan antara Self-Esteem dengan Kecenderungan Codependency dalam Pertemanan Dekat di Kalangan Mahasiswa Psikologi Universitas Negeri Padang - Yuladi, Agmal; Mardianto, Mardianto (Lembaga Yasin AlSys, 2025)
This study aims to examine the relationship between self-esteem and codependency within the context of close friendships among Psychology students at Universitas Negeri Padang. A quantitative approach with a correlational design was employed. The sample consisted of 224 students selected through purposive sampling. Instruments used included a codependency scale based on components developed by Fischer (1991) and a self-esteem scale developed by Rosenberg (1995). Data were analyzed using the Pearson Product-Moment correlation technique. The results revealed a significant negative relationship between self-esteem and codependency, indicating that higher levels of self-esteem are associated with lower tendencies toward codependent behaviors in close friendships, and vice versa. These findings suggest that strengthening self-esteem may serve as a preventive strategy for reducing unhealthy emotional dependence in students’ social relationships. This research contributes to the relational psychology literature and underscores the importance of self-esteem enhancement interventions within the context of higher education.